Soft x-ray studies of plasma-focus pinch structures in PF-1000U experiments. (13th August 2015) - Sadowski, M J; Paduch, M; Skladnik-Sadowska, E; Surala, W; Zaloga, D; Miklaszewski, R; Zielinska, E; Tomaszewski, K
Abstract: This work reports on recent experiments performed at the modernized PF-1000U plasma-focus facility. In contrast to earlier studies the main attention was focussed on measurements of the soft x-ray emission. Detailed time-integrated x-ray measurements, carried out using filtered pinhole cameras with sensitive x-ray films, are presented and analysed. The fine structure of the collapsing current sheath and dense pinch column is investigated. Observations of 'plasma filaments' are discussed and compared with those from the old POSEIDON facility. New results are time-integrated x-ray images of PF-1000U discharges with additional gas puffing, which in many cases show distinct plasma filaments and/or 'hot spots' formed inside the dense pinch column. The formation of such 'hot-spots' is explained by necking and breaking of the plasma filaments. Results of time-resolved x-ray measurements, performed outside the experimental chamber by means of scintillation probes, and inside with PIN-diodes placed behind pinholes and absorption filters, are also presented Time-resolved measurements, carried out using an old XUV framing-camera and a new soft x-ray four-frame camera (SXRFFC), are also presented and discussed. Correlations of the time-integrated x-ray images (of plasma filaments and hot spots) with time-resolved x-ray signals are discussed. The hypothesis that plasma-current filaments appear in almost all PF-type discharges is supported by pictures of radial erosion tracks on the anode front-plate after many discharges.